Sæmundr fróði and his work. The development of an authority in medieval Iceland - Miguel Diogo Andrade 1994- (2021)
Sæmundr Sigfússon inn fróði, "the Learned" (1056-1133), is one of the most controversial figures of the Icelandic eleventh and twelfth centuries. Sæmundr has been heralded, at different times, as the alleged author of the Poetic Edda (and other poems), the first Icelandic historian, a legal reformer, a powerbroker in twelfth-century politics, and the founder of a major school, among other claims with varying probability of truth. While the sources are well-known and the scholarship vast, this thesis will focus on the medieval texts which directly reference Sæmundr, to review what can be discerned of him among the extensive tradition that has formed through the centuries, and what to make of his authoritative presence. Discussion will steer clear of the study of Sæmundr as an Icelandic folk-hero, a mostly post-medieval development which bears little relation to the historical and literary texts explored here. The first part of the thesis focuses on the written tradition about Sæmundr‘s life. Special attention is dedicated to his residence in Oddi and the educational activities that may have taken place there, as well as to Sæmundr‘s involvement in the institution of Christian laws in Iceland. The second part centers on Sæmundr‘s nickname of fróði and how he developed as a figure of authority in Icelandic textual culture, at several levels: historiographical, literary, and even legal and political. The references to his purported works are discussed, bearing in mind the ultimate impossibility of verifying those claims. It is argued that there is not much that can be stated with certainty about the medieval priest or his work. Nevertheless, he probably developed as an authority within the Icelandic textual culture as early as the second half of the twelfth century, and went on to play an important role in the processes through which later textual witnesses construe their own past and its historical representation. Keywords: twelfth-century culture; the emergence of writing; medieval learned culture; authority; ...